Seek, and you will find: The influence of expectations on evaluations of physical activity - Dimmock, J.; Chatzisarantis, Nikos; Podlog, L.; Martin, T.; Iriye, H.; Jackson, B. (John Wiley and Sons Ltd, 2015)
Despite hundreds of studies on the effects of expectations on evaluations, few commentaries have focused on summarising the relevance of these findings for physical activity pursuits. Moreover, a parsimonious framework on the nature of these relationships in physical activity is yet to be developed. Such a framework is important given the significance of physical activity evaluations in predicting future physical activity participation. Based on existing models on persuasion, it is premised that the self can be persuaded by one's own expectations about physical activity and that such persuasion can support or refute those expectations. Which of these effects are created, and the extent of one's psychological and physical involvement in the creation of physical activity evaluations, is likely to hinge on motivation and ability to confirm or disconfirm expectations. Evidence from related bodies of literature is presented to support the primary tenets of the model, which is termed the expectation-to-evaluation model, and recommendations for practitioners and future research are offered.